Factors influence employee productivity in management unit at Hospital Universiti Sains Malaysia (HUSM) Kelantan / Syaza Sahira Hasni - Hasni, Syaza Sahira (2015)
This study is designed to determine the relationship between job satisfaction, leadership, employee commitment and workplace environment towards employee productivity. Employee productivity can be considered as important because employee behaviour strongly contributes to the success of an organization. An individual who has high productivity should be more positive in their work due to their sense of duty for every role. Job satisfaction also can influence the employee's attitude towards work. Employees with high levels of employee commitment are concerned with the work they carry out on their job. Leadership is the main role to encourage employees to be productive. As well as workplace environment is encouraging worker to become a great worker. This study was conducted in HUSM one of the employees has mentioned that employee productivity was one of the main issues in this organization. The respondents are all workers in the management unit. The estimated number of employees is not more and not than 300 employees in the administrative department while the total staffs in this organization is 3020. The convenient sampling technique was used in this study. I had distributed questionnaires to all departments in the management unit by my own and took about 3 weeks. The sample size was 176 workers, therefore 300 questionnaires were distributed and 150 questionnaires were returned. From the study, employee commitment and workplace environment are significant to the predictor. It can be concluded that employee commitment and workplace environment were the factors that must be focused in order to improve employee productivity. Both factors should be emphasized in future research.